Service orientation in holonic and multi agent manufacturing and robotics - Thomas, Andre; Trentesaux, Damien; Borangiu, Theodor (Studies in Computational Intelligence, 2013)
The book covers four research domains representing a trend for modern manufacturing control: Holonic and Multi-agent technologies for industrial systems; Intelligent Product and Product-driven Automation; Service Orientation of Enterprise's strategic and technical processes; and Distributed Intelligent Automation Systems. These evolution lines have in common concepts related to service orientation derived from the Service Oriented Architecture (SOA) paradigm.     The service-oriented multi-agent systems approach discussed in the book is characterized by the use of a set of distributed autonomous and cooperative agents, embedded in smart components that use the SOA principles, being oriented by offer and request of services, in order to fulfil production systems and value chain goals.   A new integrated vision combining emergent technologies is offered, to create control structures with distributed intelligence supporting the vertical and horizontal enterprise integration and running in truly distributed and global working environments.   The service value creation model at enterprise level consists into using Service Component Architectures for business process applications, based on entities which handle services. In this componentization view, a service is a piece of software encapsulating the business/control logic or resource functionality of an entity that exhibits an individual competence and responds to a specific request to fulfil a local (product) or global (batch) objective.